2009
DOI: 10.1681/asn.2009030271
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Mutation of Pkd2 Causes Cystogenesis and Upregulates β-Catenin

Abstract: Loss of polycystin-2 (PC2) in mice (Pkd2Ϫ/Ϫ ) results in total body edema, focal hemorrhage, structural cardiac defects, abnormal left-right axis, hepatorenal and pancreatic cysts, and embryonic lethality. The molecular mechanisms by which loss of PC2 leads to these phenotypes remain unknown. We generated a model to allow targeted Pkd2 inactivation using the Cre-loxP system. Global inactivation of Pkd2 produced a phenotype identical to Pkd2 Ϫ/Ϫ mice with undetectable PC2 protein and perinatal lethality.Using v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 66 publications
4
80
1
Order By: Relevance
“…pyramidal neuronal death and post-ischemic memory impairment after transient ischemic brain injury · anti-allodynic effect in inflammatory and neuropathic pain · reduced salivary gland function after radiotherapy Knowles et al, 2011;Liu et al, 2013;So et al, 2015;Tan and McNaughton, 2016 · cysts in kidney and pancreas · defects in cardiac septum · focal haemorrhage · total body edema · male reproductive tract defects · embryonic lethality Boulter et al, 2001;Kim et al, 2009;Nie and Arend, 2014;Wu et al, 1998 …”
Section: Wwwecmjournalorg O Krupkova Et Al Trp Channels In Joint Dmentioning
confidence: 99%
“…pyramidal neuronal death and post-ischemic memory impairment after transient ischemic brain injury · anti-allodynic effect in inflammatory and neuropathic pain · reduced salivary gland function after radiotherapy Knowles et al, 2011;Liu et al, 2013;So et al, 2015;Tan and McNaughton, 2016 · cysts in kidney and pancreas · defects in cardiac septum · focal haemorrhage · total body edema · male reproductive tract defects · embryonic lethality Boulter et al, 2001;Kim et al, 2009;Nie and Arend, 2014;Wu et al, 1998 …”
Section: Wwwecmjournalorg O Krupkova Et Al Trp Channels In Joint Dmentioning
confidence: 99%
“…Increased apoptosis was observed in Pkd2 transgenic mice and in Pkd2 knockout renal cells isolated from Pkd2 conditional knockout mice (88,89). Calcium influx mediated by transient receptor potential (TRP) channels in the plasma membrane triggers the cell death (90).…”
Section: Apoptosis In Pkd1 or Pkd2 Mutant Animal Modelsmentioning
confidence: 99%
“…Our work also found that loss of PC2 can increase the expression of b-catenin, axin2 and c-Myc. This suggests that PC2 may play a function role in inhibition of β-catenin-dependent Wnt signaling [44]. All of these results indicated that have shown that the loss of Pkd1 and Pkd2 account for abnormal activation of Wnt signaling pathways and cystogenesis.…”
Section: Wnt Pathwaymentioning
confidence: 78%
“…Many signaling pathways control ADPKD cyst formation such as the mammalian target of rapamycin (mTOR) [56,57], cyclic adenosine monophosphate (cAMP) [58,59], Wnt signaling pathway [44,60], G protein coupled receptor [GPCR] [61] and Signal Transducer and Activator of Transcription (STAT) signaling pathway [62] (Figure 1).…”
Section: Signaling Pathways As Targets In Pkd Treatmentmentioning
confidence: 99%
See 1 more Smart Citation